LITERATURE REVIEW : PENGARUH TANAMAN HERBAL TERHADAPPENURUNAN KADAR GLUKOSA DARAH PADA PASIEN DIABETES MELLITUS TAHUN 2021 - Rina Sumartini; Arif Susila (Jurnal Ilmu Keperawatan Indonesia, 2022)
Diabetes Mellitus (DM) is a chronic disease group characterized by increased blood sugar levels as a result of a metabolic system disorder in the body, where the pancreas is unable to produce the hormone insulin according to the body's needs. DM is a disease that can reduce the patient's quality of life to the point of death. Continuous treatment will have an impact on finances and side effects in DM patients. Lowering blood sugar levels can be done by using herbal plants, because herbal therapy has no side effects, is affordable and easy to obtain. Herbal plants commonly used are bay leaf, onion, turmeric, and saffron. The approach method used is to collect and analyze research articles on herbal plants to reduce blood glucose levels in patients with diabetes mellitus. Articles were collected through the EBSCO electronic database and Google schoolar using the keywords: herbal plants, diabetes mellitus and blood glucose. The criteria for articles used are those published in the period 2015-2020. Keywords: Diabetes Mellitus, Herbal Plants